Shadow of the hangman / Edward Marston. - Marston, Edward (Bow Street rivals series., 2016)
In this first instalment of 'The Bow Street Rivals Series' a riot breaks out in Dartmoor prison, enabling some American inmates to escape. The twin detectives Peter and Paul Skillen catch wind of a projected assassination but the target is unknown. Trouble ensues when a woman from the Home Office vanishes; a mysterious lady turns up at the archery shooting gallery; and Paul's gambling addiction worsens.